Diagnosis of malignant effusion using cell block and immunohistochemistry - Gamit, Bhavna; Dave, Deepshikha; Shahu, Neha (International Journal of Research in Medical Sciences, 2019)
The distinction between reactive mesothelial and adenocarcinoma cells specially signet ring type in serous effusions may be very difficult based only on morphological features particularly in early stage. Reactive mesothelial cells show varying degree of cytological atypia hence posing difficulty in differentiating it from adenocarcinoma cells. We report a case of 45 year old female patient presented with abdominal distension. Patient was an operated case of adenocarcinoma of stomach. Smears prepared from ascitic fluid and cell block shows large number of reactive mesothelial cells and few atypical cells. Atypical cells were immunoreactive for cytokeratin, epithelial membrane antigen and carcinoembryonic antigen. These confirmed the presence of malignant epithelial cells so we reported it as a malignant effusion.